UNEXPECTED LACK OF EFFECT OF THE INVASIVE AMERICAN MINK ON NESTING SURVIVAL OF FOREST BIRDS - Ramiro D. Crego; Rocío Fernanda Jara; Rozzi Marin, Ricardo Roberto; Jaime E. Jiménez (My University, 2021)
Nest predation by invasive mammalian predators can cause major impacts on native bird populations. The American mink (Neovison vison) was recently introduced on Navarino Island in southern Chile. The mink established as a new terrestrial mesopredator on the island with documented impacts on waterfowl breeding success. However, little is known about mink effects on forest bird’s reproduction. Here, we investigated nest-predation rate by native predators and the invasive mink on open-cup nesting forest birds by using artificial and natural nests. In six different plots, we deployed a grid (7 x 2) of 14 artificial nests spaced by 50 m and at random heights from the ground. We used camera traps in each nest to identify predators. At each plot, we estimated predator relative abundance using camera traps, Sherman traps, and bird point counts. We estimated nest survival probability as a function of nest age, concealment, distance to the river, and nest height. Additionally, we monitored 43 natural nests of five open-cup nesting bird species. Contrary to expected, mink was not a main predator of nests, depredating only one natural nest. The native raptor Chimango Caracara (Milvago chimango) was the main nest predator, preying on 39.8% artificial nests and 27.0% natural nests. We also found evidence that Chimango Caracara learned to associate the artificial nests with the egg reward. We argue that the lower abundance of mink in the forest and a mismatch between mink peak activity patterns and bird breeding phenology can result in low depredation. Mink impacts, however, may be more pervasive in summer months and on fledglings when mink activity peaks, and more research should be conducted to assess these questions. Our results are valuable to better understand mink impacts on biodiversity and to prioritize conservation actions on species more severely affected.
Keywords: American mink